Domesticating Building Fire Exit Occupancy Load Factor: The Case of Movie Theatre Waiting Areas - Sheida Bahadori; Mohammad Reza Hafezi; Saeid Bakhtiari (صفه)
This study aims to determine the occupancy load factor (m2/person) for cinema waiting areas in accordance with Iranian conditions. The occupant load factors are determined in the Fire Standards of Iran, relatively comply with international codes and standards such as the International Building Code . bearing in mind these factors may vary in different contexts, some of them may not be accurate enough for use in Iranian social, cultural and biological conditions.In order to implement the proposed idea, the required data were collected from library studies and field surveys. To achieve more accurate occupant load factors, the area of occupancy was surveyed and the maximum number of occupants was recorded through measuring and interviewing cinema managers. The average method was then used to calculate these occupant load factors. Finally, the obtained values were compared with data from library studies.The results show that the number of movie theatres in each floor is an effective factor in the value of occupant load factor. Accordingly, the waiting area for a maximum of two movie theatres have an occupant load factor of 0.38 square metres per person, and the waiting area for three movie theatres have an occupant load factor of 0.55 square meters per person. For waiting areas reserved for more than three movie theatres, the occupant load is not calculated separately, as the results show that the type and characteristic of the adjacent occupancies have effects on the occupant load factor.